2019
DOI: 10.1021/acs.langmuir.8b03621
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and Desorption of a Phospholipid from Single Microbubbles under Pulsed Ultrasound Irradiation for Ultrasound-Triggered Drug Delivery

Abstract: Microbubbles have potential for applications as drug and gene delivery systems in which the release of a substance is triggered by an ultrasonic pulse. In this paper, we discuss the adsorption and desorption of a film of phospholipid on the surface of a single microbubble under ultrasound irradiation. Our optical observation system consisted of a high-speed camera, a laser Doppler vibrometer, and an ultrasound cell; 1,2-dimyristoyl-sn-glycero-3-phosphocholine (DMPC) was used as the surfactant. The adsorption o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…As stated above, sonication has a number of limitations, in particular, the relatively broad size distribution of the microbubbles produced and inefficient and/or nonuniform incorporation of coating components. Alternative methods include electrolytic, electrohydrodynamic, laser-based, gyratory, microfluidic, and hybrid approaches, although these still suffer from relatively low production rates. Unnikrishnan et al have also recently shown that amalgamation may provide a more efficient process for incorporating targeting species into microbubble coatings, and this might offer a superior method for producing lyso-MBs.…”
Section: Resultsmentioning
confidence: 99%
“…As stated above, sonication has a number of limitations, in particular, the relatively broad size distribution of the microbubbles produced and inefficient and/or nonuniform incorporation of coating components. Alternative methods include electrolytic, electrohydrodynamic, laser-based, gyratory, microfluidic, and hybrid approaches, although these still suffer from relatively low production rates. Unnikrishnan et al have also recently shown that amalgamation may provide a more efficient process for incorporating targeting species into microbubble coatings, and this might offer a superior method for producing lyso-MBs.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it is important that the size distribution is narrow (high monodispersity), which provides a uniform response, thereby resulting in improved image quality (Talu et al, 2007;Kaya et al, 2010;Lin et al, 2016). Microbubbles are also expected to be suitable drug delivery carriers (Dijkmans et al, 2004;Unger et al, 2004;Nakata et al, 2019). Microbubbles can be ruptured to release drugs in target locations using ultrasound irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have focused on possible applications of acoustic waves for microto millimeter structures. For example, methods for altering the mechanical condition of microbubbles coated by lipid molecules have been investigated for improving drug delivery systems, 1 and vibration and shrinking at the surface of microbubbles with lipid membranes have been analyzed. 2,3 To target micromechanical conditions, various approaches have been applied for liquid phases.…”
Section: Introductionmentioning
confidence: 99%